Exploring Benzo[h]chromene Derivatives as Agents against Protozoal and Mycobacterial Infections - Mariano Walter Pertino; Alexander F. de la Torre; Guillermo Schmeda-Hirschmann; Celeste Vega Gómez; Miriam Rolón; Cathia Coronel; Antonieta Rojas de Arias; Carmen A. Molina-Torres; Lucio Vera-Cabrera; Ezequiel Viveros-Valdez (MDPI AG, 2024)
Background/Objectives: In this study, the efficacy of benzo[h]chromene derivatives as antiprotozoal and antimycobacterial agents was explored. Methods: A total of twenty compounds, including benzo[h]chromene alkyl diesters and benzo[h]chromene-triazole derivatives, were synthesized and tested against Trypanosoma cruzi, Leishmania braziliensis, L. infantum, and strains of Mycobacterium abscessus and Mycobacterium intracellulare LIID-01. Notably, compounds 1a, 1b, 2a, and 3f exhibited superior activity against Trypanosoma cruzi, with IC50 values of 19.2, 37.3, 68.7, and 24.7 µM, respectively, outperforming the reference drug benznidazole (IC50: 54.7 µM). Results: Compounds 1b and 3f showed excellent selectivity indices against Leishmania braziliensis, with SI values of 19 and 18, respectively, suggesting they could be potential alternatives to the commonly used, but more selective, miltefosine (IC50: 64.0 µM, SI: 43.0). Additionally, compounds 1a, 1b, and 3f were most effective against Leishmania infantum, with IC50 values of 24.9, 30.5, and 46.6 µM, respectively. Compounds 3f and 3h were particularly potent against various Mycobacterium abscessus strains, highlighting their significance given the inherent resistance of these bacteria to standard antimicrobials. Conclusions: The sensitivity of Mycobacterium intracellulare LIID-01 to these compounds also underscored their potential in managing infections by the Mycobacterium avium-intracellulare complex.